Characterization of Colonial cheeses from nine agro-industries in the Cantuquiriguaçu Territory – Paraná (Research, Society and Development, 2025)
The objective of this study was to characterize the production of artisanal Colonial cheeses from nine agro-industries in the Cantuquiriguaçu Territory, Paraná, Brazil. Nine producers participated in the initial mapping, of which three were registered with the Municipal Inspection Service (SIM), one was in the process of regularization, and five had no inspection or adequate structure. The cheeses were analyzed to determine the moisture and fat contents in the dry extract (GES) for classification of the cheeses according to Ordinance No. 146/1996 - Technical Regulation of Identity and Quality (RTIQ) for dairy products from MAPA. Additionally, the protein, ash, water activity (Aw), pH, instrumental color, and sensory characteristics were determined. Three cheeses were classified as high moisture and seven as medium moisture. As for the fat content in the dry extract, nine cheeses were classified as fatty, and only one was semi-fatty. The protein content was above 18.1g/100g and ash around 3.0g/100g. The pH ranged from 4.6 to 6.3 and the Aw was high between 0.89 and 0.93. The cheeses had characteristic coloration, with light and yellowish shades. The sensory characteristics varied for all evaluated attributes: rind, color, texture, consistency, odor, and flavor. Knowledge of the cheese characteristics in the region is essential for the improvement and value addition of Colonial cheese produced in the Cantuquiriguaçu Territory.